Digital Transformation Mediating Organizational Support and Administrative Service Performance - Victorio Nahuway; Deflin Tresya Nanulaitta; Victor Ringhard Pattipeilohy; Simson Melmambessy; Joice Siahaya (Univiversitas Dr. Djar Wattiheluw, 2026)
Digital transformation has become an important strategy for improving administrative services in higher education. This study examines the relationships among organizational support, digital transformation, and administrative service performance in vocational higher education. A quantitative explanatory approach was employed using data from 144 students at Politeknik Negeri Ambon, which were analyzed using path analysis. The results indicate that organizational support positively influences digital transformation and administrative service performance. However, digital transformation neither directly improves administrative service performance nor mediates the relationship between organizational support and service performance. These findings suggest that effective digital transformation requires not only technological investment but also strong institutional commitment, organizational readiness, and responsive administrative practices to achieve sustainable improvements in service quality.